Antidiabetogenic impact of bitter melon (Momordica charantia) and garlic (Allium sativum) on alloxan induced diabetic rabbit model - -, Ambiara; Aziz, Fahima Binthe; Hasan, Md Mahmudul; Rahman, Md Shajedur; Parvez, Misrat Masuma; Roy, Kishor Kumar; Haque, Md Anowarul (Asian Journal of Medical and Biological Research, 2016)
The present study was undertaken to investigate the antidiabetic effect of the Bitter melon and Garlic on Alloxan induced diabetes in experimental rabbits. At 2 to 3 months of age, rabbits were assigned into five groups (A, B, C, D and E) and each group was remained 4 rabbits. Group A was kept for control, Group B was treated with Alloxanintramuscullarly at a dose of 75mg /kg body weight, Group C was treated with bitter melon 250gm/kg body weight orally, Group D was treated with garlic 750mg/kg body weight orally, Group E treated with combined at previous dose. After acclimatization, diabetes was induced in four groups of rabbits (B, C, D and E) by administering Alloxan injection in a dose of 75mg/kg body weight (b.wt.) intramuscularlly. There was significant decreased in blood glucose level in all treated group C, D, E compared to the B group and lowest glucose was recorded in E group when treated with combined medicinal herbs and body weight was increased in all treated group C, D, E compared to the B group and highest was recorded in Dgroup while treated with those.% of PCV level and Hb gm/dl concentration was the highest in group E which was treated with both garlic and bitter melon compare to the A group. ESR was highest in group B treated with Alloxan and lowest in group E. The present study reveals that combined treatment increases body weight and decreases glucose level without affecting health of rabbits. Asian J. Med. Biol. Res. September 2016, 2(3): 402-408